Analisis Inovasi Dan Implementasi Peran Ekonomi Syariah Dalam Menghadapi Era Digital - Muhammad Rizky Dwi Kurniawan; Fauzatul Laily Nisa (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2024)
Abstract. The digital era has brought significant changes across various sectors of life, including the economy. The continuously evolving digital technology presents new opportunities and challenges, particularly in the implementation of Islamic economics in Indonesia. This article aims to analyze the innovations and implementation of Islamic economics in facing the developments of the digital era. The theoretical review covers the principles of Islamic economics, technology in the digital era, and the role of digital technology in the context of Islamic economics. This research employs a literature review method to understand various innovations and implementations in Islamic economics. The study results show that Islamic fintech, blockchain, Islamic crowdfunding, and collaboration with E-Commerce marketplaces have had a positive impact by enhancing access, transparency, and efficiency in financial transactions. By leveraging technological innovations, Islamic economics can contribute to creating an inclusive and sustainable economic system, benefiting individuals and society as a whole. Keywords: Digital Era, sharia economics, Technological Innovation Abstrak. Era digital telah membawa perubahan signifikan di berbagai sektor kehidupan, termasuk ekonomi. Teknologi digital yang terus berkembang memberikan peluang dan tantangan baru, khususnya dalam implementasi ekonomi syariah di Indonesia. Artikel ini bertujuan untuk menganalisis inovasi dan implementasi ekonomi syariah dalam menghadapi perkembangan era digital. Kajian teori mencakup prinsip-prinsip ekonomi syariah, teknologi di era digital, dan peran teknologi digital dalam konteks ekonomi syariah. Penelitian ini menggunakan metode kajian literatur untuk memahami berbagai inovasi dan implementasi dalam ekonomi syariah. Hasil studi menunjukkan bahwa fintech syariah, blockchain, crowdfunding syariah, dan kolaborasi dengan E-Commerce marketplace telah membawa dampak positif dengan meningkatkan akses, transparansi, dan efisiensi transaksi keuangan. Dengan memanfaatkan inovasi teknologi, ekonomi syariah dapat berkontribusi dalam menciptakan sistem ekonomi yang inklusif dan berkelanjutan, menguntungkan individu dan masyarakat secara keseluruhan. Kata kunci: Era Digital, Ekonomi Syariah, Inovasi Teknologi